Bauhaus and its Expressive Reflections in Contemporary Graphic Design (Journal of Namibian Studies : History Politics Culture, 2023)
This study is important because it studies the implications of the Bauhaus principles in contemporary graphic design. It aims to reveal the expressive reflections of Bauhaus in contemporary graphic design. The objective reduction is to study the Bauhaus implications in graphic poster design. The spatial limitation is Germany. As for the year 2020, the most important conditions for the title were identified, and the theoretical framework was dealt with (composition, factors of appearance, characteristics and modernity in Bauhaus). The study also touched on the most important intellectual, functional and aesthetic statements, and the ideology of the Bauhaus, which are one of the most important official statements of this school and its reflections in contemporary graphic design. The methodology, the research community and sample, and the models were analyzed, then the results and conclusions of the research were produced with recommendations and proposals.